Home-based virtual reality for chronic pain: protocol for an NIH-supported randomised-controlled trial. Issue 6 (15th June 2021) - Birckhead, Brandon; Eberlein, Sam; Alvarez, Genie; Gale, Rebecca; Dupuy, Taylor; Makaroff, Katherine; Fuller, Garth; Liu, Xiaoyu; Yu, Kyung-Sang; Black, J T; Ishimori, Mariko; Venuturupalli, Swamy; et al.
Abstract : Introduction: Chronic pain is highly prevalent and associated with a large burden of illness; there is a pressing need for safe, home-based, non-pharmacological, interventions. Virtual reality (VR) is a digital therapeutic known to be effective for acute pain, but its role in chronic pain is not yet fully elucidated. Here we present a protocol for the National Institute of Health (NIH) Back Pain Consortium (BACPAC) VR trial that evaluates the effectiveness of three forms of VR for patients with chronic lower back pain (cLBP), a highly prevalent form of chronic pain. Methods and analysis: The NIH BACPAC VR trial will randomise 360 patients with cLBP into one of three arms, each administered through a head-mounted display: 1) skills-based VR, a program incorporating principles of cognitive behavioural therapy, mindful meditation and physiological biofeedback therapy using embedded biometric sensors; 2) distraction-based VR, a program using 360-degree immersive videos designed to distract users from pain; and 3) sham VR, a non-immersive program using two-dimensional videos within a VR headset. Research participants will be monitored for 12 weeks using a combination of patient-reported outcomes administered via REDCap (Research Electronic Data Capture), wearable sensor data collected via Fitbit Charge 4 and electronic health record data. The primary outcome will be the NIH Patient-Reported Outcomes Measurement Information System (PROMIS) Pain Interference scale. Secondary outcomes will include PROMIS Anxiety, PROMIS Sleep Disturbance, opioid prescription data and Pain Catastrophizing Scale Short Form. A subgroup analysis will explore patient level predictors for VR efficacy. Ethics and dissemination: Ethics approval was obtained from the Institutional Review Board of Cedars-Sinai Health System in April 2020. The results will be disseminated in a peer-reviewed journal. Trial registration number: NCT04409353 .